TINJAUAN LITERATUR SISTEMATIS KEPEMIMPINAN DALAM MANAJEMEN PERPUSTAKAAN - Jayanti Fakhlina, Resty (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2022)
Leadership is an important component of library management. This study aims to collect and systematically analyze literature on library leadership, so that libraries as information center can provide the best services to users. The research method is a systematic literature review (SLR), collected literature using Publish or Perish (PoP), then extracted using Preferred Reporting Items for Systematic Literature Review and Meta-Analyses 2020 (PRISMA2020), then analyzed using VOSviewer. The results is the literature on library leadership was divided into 12 clusters with 244 keywords. The dominating keywords are style, diversity, assessment, staff, and framework. The conclusion of this systematic literature review research on leadership in library management states that the theme of library leadership is very interesting for researchers because library leadership does not have to follow the right leadership theory, every library leader has a unique way and has its own characteristics ranging from leadership style, assessment, diversity, and their own framework in approaching staff to achieve excellent service for users.